Educating Family Medicinal Plants (Tanaman Obat Keluarga) Efficacy Through Mobile Application - Soetam Rizky Wicaksono; Felik S.W.W Broto; Purnomo Purnomo (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2019)
Family Medicinal Plants or in Bahasa named as TOGA (Tanaman Obat Keluarga) has been a historical tradition in Indonesia for its effectiveness. most of villager merely depend on tale on how to utilize the home plants as medicine. Also, there are some hereditary habits which become their guidelines on how to make use of family medicinal plants. This community service purpose is creating mobile application for educating family medicinal plants for villager. This mobile application containing knowledge for utilizing family medicinal plants based upon scientific research and its recipe for them. Mobile application has already been published to play store and available for downloading. It also already trained to villager and disseminate by putting it in banner at village office of Petung Sewu.